Strategic Planning of Islamic Education at Muhammadiyah Terpadu Sendang Agung and SD Muhammadiyah Bandar Jaya - Yuli Supriani (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This study aims to explore and analyze the practice of strategic planning in Islamic education at two Muhammadiyah elementary schools, namely SD Muhammadiyah Terpadu Sendang Agung and SD Muhammadiyah Bandar Jaya. The background of this research departs from the importance of institutional strategies in responding to the challenges of Islamic education in the midst of social, cultural, and national education policy changes. This research uses a qualitative approach with a case study design, involving in-depth interviews, observations, and documentation as data collection techniques. The results of the study show that both schools have formulated a vision and mission that reflects Islamic values through a participatory process. The main challenges faced include limited resources, the influence of external values, and a weak understanding of strategic management. The implementation of the strategy is carried out through various religious programs and strengthening governance, but its effectiveness depends on leadership and stakeholder involvement. The evaluation of strategies typically takes an administrative approach and lacks long-term evaluative tools. This research emphasizes the importance of a comprehensive strategic evaluation system and the repositioning of policies based on data and Islamic values. These findings make a theoretical and practical contribution to the development of Islamic education management at the primary school level.